Cooperation and authoritarian values: An experimental study in China - Vollan, Bjorn; Landmann, Andreas; Zhou, Yexin; Hu, Biliang; Herrmann-Pillath, Carsten (European Economic Review, 2017)
Using samples of both students and workers in China and comparing democratic decision making (i.e. being able to choose one's rules) to non-democratic decision making (i.e. exogenously imposed rule), we show that Chinese participants cooperate the most in a public goods game under the stylized authoritarian environment. This finding may be surprising in light of previous evidence for a “democracy premium” but is in line with authoritarian norms which are prominent in China. We further show that there is a systematic association between participants’ values and their relative contribution decisions in exogenous and endogenous implementation of the rule. Our major finding is that those subjects that place greater value on accepting authority are responsible for greater levels of cooperation under top-down governance. Our findings provide evidence that the effectiveness of a political institution depends on its congruence with individual values and societal norms.
Created from Fastlane, Scopus look-up
Keywords: Authoritarian values; China; Democratic voting; Legitimacy of legal sanctions; Public goods